Inside man : the discipline of modeling human ways of being - Moldoveanu, Mihnea C. (Stanford Business Books, 2011)
'Inside Man' presents an exercise in modelling human ways of being - thinking, feeling, acting. It does not merely introduce models, but also attempts to teach modelling and produce, within the reader, the predispositions and attitudes of the modeller.